1994
DOI: 10.1093/ije/23.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Serum Albumin and Mortality in the BUPA Study

Abstract: In the British United Provident Association (BUPA) study, a prospective observational study of 21,520 men, the serum albumin of 877 men who died during 10 years of follow-up was compared with that of 877 controls, each matched to a case by age (within 1 year) and date of attendance (within 3 months). There was little overall difference (mean case-control difference = -0.11 milligram, P > 0.2) despite the fact that other studies have reported a long-term association between low serum albumin and increased morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 0 publications
1
30
1
Order By: Relevance
“…Positive associations between serum albumin levels and male sex, serum lipids and blood pressure, or inverse associations between serum albumin levels and age and smoking have been reported in previous studies [18][19][20] . Most, however, have considered serum albumin values only in relation to a few risk factors and did not adjust for possible confounders.…”
Section: Risk Factors For Cad and Acute-phase Proteins 957supporting
confidence: 56%
“…Positive associations between serum albumin levels and male sex, serum lipids and blood pressure, or inverse associations between serum albumin levels and age and smoking have been reported in previous studies [18][19][20] . Most, however, have considered serum albumin values only in relation to a few risk factors and did not adjust for possible confounders.…”
Section: Risk Factors For Cad and Acute-phase Proteins 957supporting
confidence: 56%
“…Accordingly several epidemiological studies have reported an increased risk of cancer mortality associated with low serum albumin concentrations (Phillips et al, 1989;Law et al, 1994). The results from one study on incidence of colon cancer was also in line with the hypothesis of a protective effect (Ko et al, 1994), whereas another study reported elevated serum albumin levels in patients with future colon cancer (Stevens et al, 1994).…”
Section: Introductionmentioning
confidence: 58%
“…10 -14 Previous studies have suggested that a lower concentration of serum albumin is associated with a 2-fold increased risk of total cardiovascular mortality, 6,10,[15][16][17] all-cause mortality, 10,15,16,18,19 and cancer mortality. 16,20 Contrary to these studies, Law et al 11 did not find evidence for an association between lower levels of serum albumin and mortality from cardiovascular disease or cancer.…”
mentioning
confidence: 93%